A fijivirus major viroplasm protein shows RNA-stimulated ATPase activity by adopting pentameric and hexameric assemblies of dimers - Llauger, Gabriela; Melero, Roberto; Monti, Demian Esteban; Sycz, Gabriela; Huck-Iriart, Cristian; Cerutti, Maria Laura; Klinke, Sebastián; Mikkelsen, Evelyn; Tijman, Ariel; Arranz, Rocío; Alfonso, Victoria; Arellano, Sofía Maité; et al. (American Society for Microbiology, 2023)
Fijiviruses replicate and package their genomes within viroplasms in a pro cess involving RNA-RNA and RNA-protein interactions. Here, we demonstrate that the 24 C-terminal residues (C-arm) of the P9-1 major viroplasm protein of the mal de Río Cuarto virus (MRCV) are required for its multimerization and the formation of viroplasm like structures. Using an integrative structural approach, the C-arm was found to be dis pensable for P9-1 dimer assembly but essential for the formation of pentamers and hexamers of dimers (decamers and dodecamers), which favored RNA binding. Although both P9-1 and P9-1DC-arm catalyzed ATP with similar activities, an RNA-stimulated ATPase activity was only detected in the full-length protein, indicating a C-arm-mediated interaction between the ATP catalytic site and the allosteric RNA binding sites in the (do)decameric assemblies. A stronger preference to bind phosphate moieties in the dec amer was predicted, suggesting that the allosteric modulation of ATPase activity by RNA is favored in this structural conformation. Our work reveals the structural versatility of a fijivirus major viroplasm protein and provides clues to its mechanism of action.